Investigating the Prevalence and Types of Clinical Services Offered by Pharmacists in Federally Qualified Health Centers in South Carolina: A Qualitative, Cross-Sectional Survey - Brice Laney; Anna Rayfield; Reagan K. Barfield; Paul Brandon Bookstaver; Natalie Nelson; Kaitlyn Phillips; Carrington Royals (SAGE Publishing, 2024)
Purpose: To investigate the prevalence and type of clinical pharmacy services offered within South Carolina Federally Qualified Health Centers (SC FQHCs) and identify existing implementation barriers. Methods: This study was a cross-sectional survey of pharmacists or Chief Medical Officers practicing in SC FQHCs. Organizations were identified utilizing the Health Resources and Services Administration (HRSA) database and were contacted to participate in a telephone survey. An electronic form was created in REDCap ® software. Descriptive statistics were used to analyze and evaluate data. Results: Twenty-two SC FQHCs were eligible for the survey, with 16 (72.7%) participating. Of the respondents, 9 (56%) offered at least 1 service. The most common services offered were chronic disease state management, diabetes self-management education and support (DSMES), and tobacco cessation (43.8%, n = 7). The least common services offered were chronic care, Hepatitis C, and HIV management (18.9%, n = 3). The most common barriers to implementation were lack of personnel and provider interest (62.5%, n = 10). The least common barrier was a lack of pharmacist interest or time (25%, n = 4). Conclusion: Pharmacists offered at least 1 clinical service within most SC FQHCs. Barriers were identified that prevented expansion of services and further research is needed to overcome these.